Desain Pembelajaran Inovatif Menggunakan Pendekatan Deep Learning Berbasis Artificial Intelligence (AI) Terhadap Extending Knowledge Mahasiswa Di Era Society 5.0 - A.M, Muh. Inayah; Anas, Munawir; Resa, Asmirinda; Ampry, Evy Segarawati; Agung, Agung; Magfirah, Nur (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The Society 5.0 era drives higher education institutions to transform through the utilization of advanced technologies, including Artificial Intelligence (AI) and deep learning approaches, in order to produce graduates who are both adaptive and globally competitive. This study aims to design and evaluate the effectiveness of an innovative learning model employing AI-based deep learning to enhance the extending knowledge of undergraduate students in the Elementary School Teacher Education (PGSD) program at Universitas Sulawesi Barat. The primary focus is to examine how AI integration can strengthen students’ critical analysis, creativity, and digital collaboration skills. A mixed-methods approach with a convergent design was applied, where quantitative data were collected through surveys of more than half of the 2024 cohort (±100 students) and 15 lecturers, while qualitative data were obtained from semi-structured interviews and classroom observations. Survey findings reveal that AI integration in the learning process and the ease of technology access fall into the high category (means of 4.18 and 4.05, respectively), whereas AI support for personalized learning is rated moderate–high (mean 3.92). The implementation of AI significantly improved critical analysis (mean 4.22) and digital collaboration (mean 4.11), although student creativity remained moderate (mean 3.88) due to a tendency to rely on AI systems. Qualitative results corroborate the quantitative data, indicating increased active participation and student confidence, while also highlighting the need for pedagogical strategies to stimulate original ideas. Overall, the study concludes that an innovative learning design grounded in AI-based deep learning effectively broadens extending knowledge and fosters twenty-first-century competencies, offering implications for curriculum development, faculty training, and digital infrastructure. Future research is recommended to integrate project-based or inquiry-driven approaches to further optimize student creativity.